2020
DOI: 10.46717/igj.53.2d.2ms-2020-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Biostratigraphic Analysis of the Oligocene-Early Miocene Successions From Sulaimani Area, Kurdistan Region, Iraq

Abstract: Three sections (Darzila, Hazar Kani and Basara) of the Oligocene –Early Miocene successions from Sulaimani area, Kurdistan region-NE Iraq, were measured and studied in order to interpret the biostratigraphic zonations at the Low and High Folded Thrust zones boundary, Low Folded Thrust zone, which are integrated with strontium stratigraphic dating. Accordingly, five biozones have been identified and they are:1- Nummulites vascus- Nummulites intermedius- Nummulites fichteli Assemblage Zone (Shallow Benthic Zone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…The age of this zone indicates Early Turonian, which is equivalent to that of Abdel-Kareem et al (1996) [29], [17], and the older part of Globotruncana helvetica zone of Youkhanna (1976) [9], Postuma (1971) [16]. this zone is also equivalent to that proposed by Lawa and Al-Khafaf (2022) [6], Hussain and Al-Sheikly (2015) [30], and Al-Khafaf (2014) [31], also this zone corresponds to the older part of Marginotruncana helvetica zone of Ghafor et al (2004) [32], Ghafor (1993) [33].…”
Section: Biostratigraphic Zonationssupporting
confidence: 59%
See 3 more Smart Citations
“…The age of this zone indicates Early Turonian, which is equivalent to that of Abdel-Kareem et al (1996) [29], [17], and the older part of Globotruncana helvetica zone of Youkhanna (1976) [9], Postuma (1971) [16]. this zone is also equivalent to that proposed by Lawa and Al-Khafaf (2022) [6], Hussain and Al-Sheikly (2015) [30], and Al-Khafaf (2014) [31], also this zone corresponds to the older part of Marginotruncana helvetica zone of Ghafor et al (2004) [32], Ghafor (1993) [33].…”
Section: Biostratigraphic Zonationssupporting
confidence: 59%
“…Youkhanna (1976) [9] indicated Turonian-Santonian age and divided it into 3 biozones. Al-Dhaif (1997) [10] in the Jambour field, Abawi and Hammoudi (1997) [3] in the Kirkuk area, North Iraq, and Al-Khafaf (2005) [11] in the Dokan-Endezah areas studied the foraminiferal biostratigraphy of Kometan Formation and indicates Late Turonian-Early Campanian age., Lawa and Al-Khalaf (2022) [6] studied the Dokan, Guneri and lower part of Kometan Formation in Kosrat anticline, and indicated unconformity at the base and top of the Gulneri Formation with both Dokan and Gulneri Formations. In contrast to the unconformable boundary of the Gulneri and Kometan formations, Karim, and Taha (2009 b) [12] proved the conformable boundaries of the Gulneri Formation and the absence of unconformity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…studied the biostratigraphy of planktic foraminifera fossils of period the lower Turonian-lower Maastrichtian and determined the age of the Gulneri Shale Formation of lower Turonian-upper Turonian, and the Kometan Formation of lower Turonian-lower Campanian, and Mushorah Formation from the lower Santonian-lower Campanian, while [4] studied the biostratigraphy of the Gulneri Shale Formation and the lower part of the Kometan Formation in the Kosrat fold in northeastern Iraq, and showed that the Gulneri Shale Formation consists of the black shale and a thickness of about 1.5 m, which reflects the events of OAE _ 2, and that the lower and upper contact surfaces of the formation are unconformity with the Dokan Formation underline it and the Kometan Formation above it and determined its age with lower Turonian, [5] by studying the paleoenvironment of the Kometan Formation in the Dokan area, concluded that the formation was deposited in a deep marine environment depending on the masses of Ostracoda and some types of foramnifra. , The study area included two subsurface sections within the Dome of Daoud in the Bai Hassan field in northern Iraq, consisting of two wells (BH-16 and BH-86) as shown in Table (1) [6] and located within the Low Folded Zone within the Western Zagros Fold -Thrust Belt according to the tectonic divisions of Iraq [7] Fig ( 1).…”
mentioning
confidence: 99%